CCL5 production in lung cancer cells leads to an altered immune microenvironment and promotes tumor development. (1st January 2022) - Melese, Etienne S.; Franks, Elizabeth; Cederberg, Rachel A.; Harbourne, Bryant T.; Shi, Rocky; Wadsworth, Brennan J.; Collier, Jenna L.; Halvorsen, Elizabeth C.; Johnson, Fraser; Luu, Jennifer; Oh, Min Hee; Lam, Vivian; et al.
ABSTRACT: Current immunotherapies for lung cancer are only effective in a subset of patients. Identifying tumor-derived factors that facilitate immunosuppression offers the opportunity to develop novel strategies to supplement and improve current therapeutics. We sought to determine whether expression of driver oncogenes in lung cancer cells affects cytokine secretion, alters the local immune environment, and influences lung tumor progression. We demonstrate that oncogenic EGFR and KRAS mutations, which are early events in lung tumourigenesis, can drive cytokine and chemokine production by cancer cells. One of the most prominent changes was in CCL5, which was rapidly induced by KRAS G12V or EGFR L858R expression, through MAPK activation. Immunocompetent mice implanted with syngeneic KRAS-mutant lung cancer cells deficient in CCL5 have decreased regulatory T cells (Tregs ), evidence of T cell exhaustion, and reduced lung tumor burden, indicating tumor-cell CCL5 production contributes to an immune suppressive environment in the lungs. Furthermore, high CCL5 expression correlates with poor prognosis, immunosuppressive regulatory T cells, and alteration to CD8 effector function in lung adenocarcinoma patients. Our data support targeting CCL5 or CCL5 receptors on immune suppressive cells to prevent formation of an immune suppressive tumor microenvironment that promotes lung cancer progression and immunotherapy insensitivity.